When is it safe to return to sport after ACL reconstruction? Reviewing the criteria - Kaplan, Y.; Witvrouw, E. (Sports Health: A Multidisciplinary Approach, 2019)
Context: There is an ever-increasing trend toward sports, fitness, and recreation activities, so the incidence of anterior cruciate ligament sports injuries has increased. Perhaps the greatest challenge for sports clinicians is to return the injured athlete back to his/her original sport at an even greater level of functional ability than preinjury. For this, rigorous and well-researched criteria are needed.